Chiroptical‐Conjugated Polymer/Chiral Small Molecule Hybrid Thin Films for Circularly Polarized Light‐Detecting Heterojunction Devices. (28th January 2019) - Kim, Na Yeon; Kyhm, Jihoon; Han, Hyemi; Kim, Soo Jin; Ahn, Jongtae; Hwang, Do Kyung; Jang, Ho Won; Ju, Byeong‐Kwon; Lim, Jung Ah
Abstract: Herein, a simple and facile strategy is described to obtain chiroptically active semiconductor thin films by blending of poly(3‐alkylthiophene)s, which are conventional achiral polymer semiconductors, and 1, 1′‐binaphthyl (BN), a versatile chiral molecule. As expected, the intermolecular interaction between the two materials is important to extend the chirality of the binaphthyl molecules to the hybrid films. The controlled phase separation and crystallization of poly[3‐(6‐carboxyhexyl)thiophene‐2, 5‐diyl] (P3CT) and binaphthyl hybrid films result in unique heterojunction bilayer thin‐film structures that consisted of BN microcrystals at the top and a P3CT/BN mixed layer at the bottom. Such heterojunction bilayer films exhibit significantly amplified chiroptical response with weak broadened tails, which is due to the enhanced crystallization of the chiral BN molecules and formation of heteroaggregates in the hybrid films. Based on the characterization of crystalline structure and photoluminescence analysis, it is found that new electronic energy states are formed in the conduction band region of P3CTs in the P3CT/BN heteroaggregates, which contribute to chirality transfer from BN to the hybrid films. As a proof of concept, a photodiode capable of distinguishably sensing the left‐ and right‐handed circularly polarized light is successfully fabricated by using the hybrid films with the heterojunction bilayer structure. Abstract : Chiroptical‐conjugated polymer hybrid thin films with heterojunction structures are realized by simple blending of poly(3‐alkylthiophene)s, which are conventional achiral polymer semiconductors, and 1, 1′‐binaphthyl derivative, which is a versatile chiral molecule. A photodiode based on this hybrid film with a heterojunction bilayer structure can distinguish between left‐ and right‐handed circularly polarized light.